Receptor-Mediated Melanoma Targeting with Radiolabeled α-Melanocyte-Stimulating Hormone: Relevance of the Net Charge of the Ligand - Bapst, Jean-Philippe; Eberle, Alex N. (Frontiers in Endocrinology, 2017)
A majority of melanotic and amelanotic melanomas overexpress melanocortin type 1 receptors (MC1R) for α-melanocyte stimulating hormone (α-MSH). Radiolabeled linear or cyclic analogs of α-MSH have a great potential as diagnostic or therapeutic tools for the management of malignant melanoma. Compounds such as [111In]DOTA-NAP-amide exhibit high affinity for the MC1R in vitro, good tumor uptake in vivo, but they may suffer from relatively high kidney uptake and retention in vivo. We have shown previously that the introduction of negative charges into radiolabeled DOTA-NAP-amide peptide analogs may enhance their excretion and reduce kidney retention. To address the question of where to place negative charges within the ligand, we have extended these studies by designing two novel peptides, Ac-Nle-Asp-His-D-Phe-Arg-Trp-Gly-Lys(DOTA)-D-Asp-D-Asp-OH (DOTA-NAP-D-Asp-D-Asp) with three negative charges at the C-terminal end (overall net charge of the molecule −2), and DOTA-Gly-Tyr(P)-Nle-Asp-His-D-Phe-Arg-Trp-NH2 (DOTA-Phospho-MSH2-9) with two negative charges in the N-terminal region (net charge −1). Whereas the former peptide showed markedly reduced receptor affinity and biological activity by >10-fold compared to DOTA-NAP-amide as reference compound, the latter peptide displayed similar bioactivity and receptor affinity as the reference compound. The uptake by melanoma tumor tissue of [111In]DOTA-Phospho-MSH2-9 was 7.33 ± 0.47 %ID/g 4 h after injection, i.e. almost equally high as with [111In]DOTA-NAP-amide. The kidney retention was 2.68 ± 0.18 %ID/g 4 h after injection and hence 44% lower than that of [111In]DOTA-NAP-amide. Over an observation period from 4−48 h, the tumor-to-kidney ratio of [111In]DOTA-Phospho-MSH2-9 was 35% more favorable than that of the reference compound. In a comparison of DOTA-NAP-D-Asp-D-Asp, DOTA-Phospho-MSH2-9 and DOTA-NAP-amide with five previously published analogs of DOTA-NAP-amide that altogether cover a range of peptides with an overall net charge between +2 and −2, we now demonstrate that a net charge of −1, with the extra negative charges preferably placed in the N-terminal region, has led to the lowest kidney uptake and retention. Charges of +2 or −2 markedly increased kidney uptake and retention. In conclusion, the novel DOTA-Phospho-MSH2-9 may represent a new lead compound for negatively charged linear MC1R ligands that can be further developed into a clinically relevant melanoma targeting radiopeptide.